Accuracy of the Kato-Katz and direct examination in the diagnosis of worms in preserved feces - Gunasari, Lala Foresta Valentine; Triana, Dessy; Reyudo Suringgar, Sadid (BKM Public Health and Community Medicine, 2021)
Purposes: Soil-transmitted helminth (STH) causes helminthiasis with an incidence of 24% in the world's population. Children aged 2-14 years are the population most susceptible to helminthiasis. In Indonesia, there are 60.4 million children who have worms. Worms can cause delays in the growth and development of children. Worms can be diagnosed through a qualitative (direct examination) and quantitative (Kato-Katz) stool examination. This study aimed to analyze the accuracy of stool examination results using the Kato-Katz method and the Direct Examination method on 10% formalin-preserved feces. Methods: The research design used an observational study with diagnostic tests. The research subject amounted to 140 samples of 10% formalin preserved feces for 13 months. Examination of preserved stool specimens used the Kato-Katz and Direct Examination methods and was observed using a light microscope. Results: The results showed that 45,71% were infected with STH using the Kato-Katz method and direct examination of 35.71%. The accuracy test showed that the sensitivity and specificity values of the Kato-Katz method were 86.79% and 79.31%, respectively. The direct examination was obtained by 64.15% and 81.60%. Conclusions:The Kato-Katz method is more sensitive than the direct examination method in diagnosing helminthiasis in preserved feces, but the direct examination method has a higher specificity value than the Kato-Katz method.